2000
DOI: 10.1007/s002230050014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of In Vivo Bone Mineral Measurements in Sheep Using Dual-Energy X-ray Absorptiometry

Abstract: We evaluated the precision and accuracy of in vivo measurements of spine bone mineral density (BMD) and bone mineral content (BMC) in five ewes using dual-energy X-ray absorptiometry (DXA, Lunar DPX-L). The short-term in vivo reproducibility expressed as the coefficient of variation (CV) varied from 0.9 to 1.6% for spine BMD and from 1 to 3.1% for spine BMC. The ex vivo measurements, performed in 20 cm of water to simulate soft tissue thickness, correlated closely with the in vivo measurements, yielding an r v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…They aimed to provide further information on some qualitative and quantitative bone characteristics that cannot be obtained from patients enrolled in clinical trials (Turner et al, 1995a;b;c;Hartke, 1998;Fini et al, 2000). The ovariectomized sheep, which had already been witlely used for endocrinological veterinary studies (Dobson et aZ., 1999;Harris et al, 2000;Keller-Wood, 2000), was proposed as a model of human osteoporosis, because it seemed to be promising for studying bone turnover, the therapeutic effects of innovative pharmacological treatments and biomaterial osteointegration in postmenopausal osteoporosis (Newman et al, 1995;Thompson et al, 1995;Turner et al, 1995a;b;c). Such model is characterised by high bone turnover, increased osteoclastic activity, perforation of trabeculae and endosteal resorption, which all make the bone marrow cavity become larger (Hartke, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They aimed to provide further information on some qualitative and quantitative bone characteristics that cannot be obtained from patients enrolled in clinical trials (Turner et al, 1995a;b;c;Hartke, 1998;Fini et al, 2000). The ovariectomized sheep, which had already been witlely used for endocrinological veterinary studies (Dobson et aZ., 1999;Harris et al, 2000;Keller-Wood, 2000), was proposed as a model of human osteoporosis, because it seemed to be promising for studying bone turnover, the therapeutic effects of innovative pharmacological treatments and biomaterial osteointegration in postmenopausal osteoporosis (Newman et al, 1995;Thompson et al, 1995;Turner et al, 1995a;b;c). Such model is characterised by high bone turnover, increased osteoclastic activity, perforation of trabeculae and endosteal resorption, which all make the bone marrow cavity become larger (Hartke, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are available in the literature on sheep osteopenic models: most of them were conducted 6 months after ovariectomy and mainly concentrated on the iliac crest using histomorphometric and mechanical measurements (Pastoureau et al, 1991;Newman et al, 1995;Turner et aZ., 1995b;c;1999;Fini et al, 2000). Moreover, no author provided a complete assessment of the lumbar vertebrae or other sites, by static and dynamic histomorphometry in addition to mechanical and densitometric evaluations and no significant correlation between different methods was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extent of published studies covering the use of DXA with rodents we elected to avoid their inclusion in this chapter except in a few instances for comparison. DXA has been used with species of agricultural concern including sheep (Mercier et al, 2006;Ponnampalam et al, 2007;Pouilles et al, 2000;Turner et al, 1995a), pigs (Clarys et al, 2010;Elowsson et al, 1998;Lee et al, 2011;Losel et al, 2010;Lukaski et al, 1999;Mitchell et al, 1998;Nielson et al, 2004), horses (McClure et al, 2001;Secombe et al, 2002), goats (Corten et al, 1997), and cattle (Zotti et al, 2010). Additionally, DXA has been applied to wildlife such as the grizzly bear (Felicetti, 2003 as cited in Stevenson & van Tets, 2008).…”
Section: Dxa Use With Animalsmentioning
confidence: 99%
“…Therefore, an initial study was performed as part of this work to justify the use of RP models by comparing the ultimate strength and visual failure mechanisms of RP models with those of corresponding real bone specimens. Ovine trabecular bone specimens were used since previous studies have shown that this provides an appropriate large animal model for analysis of the mechanical behaviour of bone (Newton et al, 2004;Pouilles et al, 2000;Thomas et al, 1996).…”
Section: Introductionmentioning
confidence: 99%